Cytotoxic Components in an Extract from the Leaves and Stems of Stauntonia hexaphylla - Jing Zhao; Soon Ho Yim; Jung In Um; Si Hwan Park; Eun Sang Oh; Da Woon Jung; Darren R. Williams; Ik Soo Lee (Natural product sciences, 2014)
An investigation was carried out to identify novel anti-cancer compounds from Korean indigenous plant extracts. Bioassay-guided fractionation and chemical investigation of the EtOAc extract from the leaves and stems of Stauntonia hexaphylla resulted in the isolation of two active compounds, hederagenin 3-O-a-L-arabinoside (1) and quercetin (2). The structures of these compounds were elucidated by spectroscopic methods, including UV, IR, MS, NMR techniques and compared with previous spectroscopic data. The cytotoxic effects of fractions and compounds on HCT116 human colon cancer cells were evaluated using the MTT assay. Quercetin showed a stronger anti-cancer effect when compared to hederagenin 3-O-a-L-arabinoside. KCI Citation Count: 1